Association Between hMLH1 Promoter Methylation and Risk of Gastric Cancer: A Meta-Analysis - Ye, Peng; Shi, Yu; Li, Anling (Frontiers in Physiology, 2018)
Background: Human mutL homolog 1 (hMLH1) is located on chromosome 3q21-23. As a classic tumor suppressor gene, many researchers have studied the association between hMLH1 promoter methylation and gastric cancer, but their conclusions were not always consistent. Therefore, we performed a meta-analysis to make a more integrated and precise estimate of the associations. Method: PubMed, EMBASE and Cochrane Library were retrieved without language restrictions. Data were analyzed by Review Manager 5.2 and Stata 12.0 software. Odds ratio (OR) with 95% confidence interval (95%CI) was used to assess the statistical associations. Result: A total of 39 studies published before January 20, 2018 were included in this study. The results indicated that the frequency of hMLH1 promoter methylation in gastric cancers was substantially higher than that in non-cancer controls (OR = 7.94, 95%CI = 4.32-14.58, P < 0.001). Furthermore, hMLH1 promoter methylation had considerable associations with lymph node metastasis, microsatellite instability (MSI) and low expression of hMLH1 protein (OR = 1.53, 95%CI = 1.04-2.26, P = 0.03; OR = 15.33, 95%CI = 9.26-25.36, P < 0.001; OR = 37.86, 95%CI = 18.03-79.50, P < 0.001, respectively). No association was found between hMLH1 promoter methylation and Lauren classification or Helicobacter pylori (HP) infection status. Conclusion: The present study provides evidence that promoter methylation of hMLH1 is a major causative event in the occurrence and development of human gastric cancer.